2013
DOI: 10.1155/2013/575604
|View full text |Cite
|
Sign up to set email alerts
|

The Liver X Receptor in Correlation with Other Nuclear Receptors in Spontaneous and Recurrent Abortions

Abstract: The liver X receptors (LXRs) have been shown to be crucially involved in maternal-fetal cholesterol transport and placentation. The aim of this study was to investigate the expression pattern and frequency of LXR under normal physiological circumstances and in spontaneous abortion and/or recurrent miscarriage. A total of 29 (12 physiologic pregnancies/10 spontaneous abortions/7 recurrent miscarriages) human pregnancies in first trimester were analysed for LXR expression. Expression changes were evaluated by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Specimens were dehydrated in an ascending alcohol gradient and cover slipped with Eukitt ® quick hardening mounting medium (Sigma Aldrich, St. Louis, Missouri; USA). Positive control (human colon tissue) as well as negative control staining was carried out as described previously [10,37]. All slides were analyzed using the microscope Leitz Wetzlar (Germany; Type 307-148.001 514686).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were dehydrated in an ascending alcohol gradient and cover slipped with Eukitt ® quick hardening mounting medium (Sigma Aldrich, St. Louis, Missouri; USA). Positive control (human colon tissue) as well as negative control staining was carried out as described previously [10,37]. All slides were analyzed using the microscope Leitz Wetzlar (Germany; Type 307-148.001 514686).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Heterodimer partners are e.g. peroxisome proliferatoractivated receptor (PPAR), thyroid hormone receptor (TR), and liver X receptor (LXR) [2,[10][11][12]. Especially the expression of the isoform PPAR is linked to trophoblast invasion [13] and downregulation of the isoform RXRα seems to protect from apoptosis in human trophoblasts [9].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These nuclear receptors are crucially involved in maintaining a viable pregnancy, their role had been clarified especially in human trophoblastic tissue: Toth et al showed that extravillous trophoblast (EVT) in placentas of miscarriages show a significantly higher expression of RXRα in comparison to EVT in placentas of elective termination of healthy pregnancies. 13 Recent studies showed that LXR expression is decreased in miscarriage 14 and PPARγ is increased in EVT of abortive tissue. 15 …”
Section: Introductionmentioning
confidence: 99%
“…1) 26 . Negative controls were performed by replacement of the primary antibodies by species specific isotype control antibodies (Dako) as described previously 27 . In addition, the IgG negative control was performed with unspecific isotype control IgG antibodies in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%